A novel detergent-based decellularization combined with carbodiimide crosslinking for improving anti-calcification of bioprosthetic heart valve. (24th May 2021) - Luo, Yu; Huang, Shenyu; Ma, Lie
Abstract: Currently, valve replacement surgery is the only therapy for the end-stage valvular diseases because of the inability of regeneration for diseased heart valves. Bioprosthetic heart valves (BHVs), which are mainly derived from glutaraldehyde (GA) crosslinked porcine aortic heart valves or bovine pericardium, have been widely used in the last decades. However, it is inevitable that calcification and deterioration may occur within 10–15 years, which are still the main challenges for the BHVs in clinic. In this study, N-Lauroylsarcosine sodium salt (SLS) combined with N-(3-Dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) were utilized to decellularize and crosslink the heart valves instead of GA treatment. The obtained BHVs exhibited excellent extracellular matrix stability and mechanical properties, which were similar with GA treatment. Moreover, the obtained BHVs exhibited better in vitro biocompatibilities than GA treatment. After subcutaneous implantation for 30 d, the obtained BHVs showed mitigated immune response and reduced calcification compare with GA treatment. Therefore, all the above results indicated that the treatment of SLS-based decellularization combined with EDC/NHS crosslink should be a promising method to fabricate BHVs which can be used in clinic in future.